'A validation of my pedagogy': how subject discipline practice supports early career teachers' identities and perceptions of retention. Issue 4 (8th August 2021) - Morris, Julia E.; Imms, Wesley
ABSTRACT: For secondary school teachers, developing a teacher identity is complicated by spoken or implied expectations of the need to be an expert in the skills and knowledge of one's subject discipline. Since 2009, the Teacher as Practitioner study ( N = 764) has explored the effect of continued subject discipline practice on teachers' identity and retention using a longitudinal mixed-method design. Within the population are 305 responses from initial teacher education graduates classified as early career teachers, those within their first five years of teaching. This sub-sample was used to explore relationships between discipline practice, identity and perceptions of retention in the profession. Analysis of quantitative data showed time spent engaged in practice had a greater effect on expectations of retention and identity than simply aspiring to maintain a discipline practice, while qualitative analysis showed maintaining a practice in a supportive community was also highly valued.